2017
DOI: 10.2298/vsp150626146s
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between outpatient antibiotic use and the prevalence of bacterial infections in Montenegro

Abstract: Use of antibiotics in Montenegro in 2012 was more than double than necessary according to prevalence of bacterial infections and average duration of treatment. The structure of antibiotics was not in full compliance with the national good practice guidelines, but it was in accordance with data on bacterial antibiotic resistance in outpatient practice. It is necessary to initiate measures to rationalize the use of antibiotics both in terms of quantity and in terms of the structure of the most used antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
2
2
Order By: Relevance
“…40 However, nearly approachable result with study from Croatia (3.29 DDD/1000 inhabitants per day). 41 Unlike the study from Tanzania, 37 and Montenegro 38 where the penicillins, quinolones and tetracycline were consumed most frequently, in the current study tetracycline (doxycycline) was consumed most frequently (1.59 DDD/100 outpatients per day) followed by fluoroquinolones (1.48 DDD/100 outpatients per day) and penicillins (1.13 DDD/100 outpatients per day). This difference in volume of consumption may be related to short data collection period (two months) in the current study.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…40 However, nearly approachable result with study from Croatia (3.29 DDD/1000 inhabitants per day). 41 Unlike the study from Tanzania, 37 and Montenegro 38 where the penicillins, quinolones and tetracycline were consumed most frequently, in the current study tetracycline (doxycycline) was consumed most frequently (1.59 DDD/100 outpatients per day) followed by fluoroquinolones (1.48 DDD/100 outpatients per day) and penicillins (1.13 DDD/100 outpatients per day). This difference in volume of consumption may be related to short data collection period (two months) in the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…The overall antibiotic consumption volume was 5.31 DDD/100 outpatients per day. This was lower than reports from other countries, such as Tanzania (4.99 DDD/1000 inhabitants per day), 37 Montenegro (39.05 DDD/1000 inhabitants/day), 38 Slovenia (59.8 DDD/1000 inhabitants per day), 39 and Syria (20.13 DDD/1000 inhabitants per day). 40 However, nearly approachable result with study from Croatia (3.29 DDD/1000 inhabitants per day).…”
Section: Discussioncontrasting
confidence: 57%
“…This may again be linked to an increased resistance to narrow-spectrum antibiotics. Šahman-Zaimović et al found that, in cases of high resistance to amoxicillin, amoxicillin/clavulanic acid is recommended [ 35 ]. The broad-spectrum antibiotic dispensing rates in this study are high.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that antibiotic use and antibiotic resistance patterns are correlated [1820] and surveillance data on country-level antibiotic use are needed to support policies that aim to reduce antibiotic resistance. Although several studies have attempted to assess antibiotic use in China [2124], none has reported quarterly data and the influencing factors of inpatient antibiotic consumption.…”
Section: Introductionmentioning
confidence: 99%